A drowning abdomen-a case report on acute urinary retention due to retroverted gravid uterus - Marimuthu, Sangeetha; Ushadevi Gopalan; Divya Ayyanar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Acute urinary retention due to retroverted gravid uterus is a rare condition, but serious complication of pregnancy. It usually occurs between 10 and 16 weeks of gestation. We report a case of 26 year old primigravida at 13 weeks of gestation presented to OPD with the complaints of abdominal distension for 30 days and lower abdominal pain associated with burning micturition for 10 days. On examination, abdomen is uniformly distended corresponding to 30 to 32 weeks of gestation which is tense and cystic, on per vaginal examination -features of retroverted uterus felt. Scan showed single intrauterine gestation corresponding to 13 weeks+5days with full bladder. Patient was catheterised and 2.5litre of urine drained. Patient was asked to lie in prone position at least 3-4 times a day. After 1 week patient was symptomatically better, on per vaginal examination uterus returned to midposition.